2018 21st International Conference on Information Fusion (FUSION) 2018
DOI: 10.23919/icif.2018.8455482
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Odometry on Handheld Smartphones

Abstract: Building a complete inertial navigation system using the limited quality data provided by current smartphones has been regarded challenging, if not impossible. This paper shows that by careful crafting and accounting for the weak information in the sensor samples, smartphones are capable of pure inertial navigation. We present a probabilistic approach for orientation and use-case free inertial odometry, which is based on doubleintegrating rotated accelerations. The strength of the model is in learning additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 26 publications
(35 reference statements)
0
54
0
Order By: Relevance
“…As inputs we use the three-axis gyroscope and accelerometer data from a smartphone. This data is passed to an inertial navigation system (labeled 'INS' and adopted following [3]) doing statistical inference on the current 3D position, velocity, and orientation. The blocks ' ş ', 'ö', and 'g' denote integration, rotation, and gravity, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As inputs we use the three-axis gyroscope and accelerometer data from a smartphone. This data is passed to an inertial navigation system (labeled 'INS' and adopted following [3]) doing statistical inference on the current 3D position, velocity, and orientation. The blocks ' ş ', 'ö', and 'g' denote integration, rotation, and gravity, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper we take a different approach and, instead of trying to solve the inertial navigation problem end-to-end using neural networks like [5], we aim at combining machine learning based speed estimation with a classical method [3], which is based on probabilistic sensor fusion using extended Kalman filtering (EKF). That is, we build upon recent work [3], which has shown that utilizing automatic zero-velocity updates (ZUPTs) and pseudo-measurements for limiting momentary speed can give accurate trajectory estimates in varying use cases. However, often in free handheld movement ZUPTs can not be established frequently enough to constrain motion sufficiently.…”
Section: Arxiv:180803485v1 [Cscv] 10 Aug 2018mentioning
confidence: 99%
See 2 more Smart Citations
“…The rotation matrix R(t 2 ) is then formed as the direction cosine matrix corresponding to the quaternion q(t 2 ) (see, e.g., [26]). In theory, the translation could also be recovered using an accelerometer [31,7,10,21]. However, this requires knowledge of the initial velocity of the camera, or alternatively, known stationary points or reference points which can be used to aid zero-velocity updates or position updates in a Kalman filter [21].…”
Section: Rotation From Gyroscope Measurementsmentioning
confidence: 99%